Manajemen Digital Marketing PLN pada Program Diskon Tambah Daya Belakang Padang - Hay Rany; Immanuel Zai (Jurnal Abdimas Multidisiplin, 2026)
Purpose: This Community Service Program (Pengabdian kepada Masyarakat/PkM) implemented digital marketing management to support PLN’s Power Capacity Upgrade Discount program during National Customer Day at PLN Unit Layanan Pelanggan (ULP) Belakang Padang, Batam. The program focused on improving the effectiveness of digital promotion, increasing customer awareness of PLN’s digital services, and strengthening institutional communication in the context of border areas. Methodology/approach: The program was conducted from September to December 2025 at PLN ULP Belakang Padang, Indonesia. The methods included field observation, community training, the development of digital promotional content incorporating Malay cultural elements, and social media campaigns through official PLN platforms. Program evaluation used social media analytics and PLN Mobile application usage data to compare the conditions before and after implementation. Results/findings: The results indicate a 45% increase in customer engagement with promotional content, measured using interaction metrics such as likes, comments, and shares. The PLN Mobile application usage increased by 20% based on internal access data during the campaign period. Program targets were achieved, with nine customers successfully utilizing the Power Capacity Upgrade Discount. Conclusions: The digital marketing approach was effective in enhancing customer engagement and awareness of PLN digital services. Limitations: The limitations of this study include uneven digital literacy levels and a short implementation period. Contributions: This program provides an applicable model of digital-based community service for public organizations in border regions.